Pengaruh Penambahan Limbah Cair Pabrik Kelapa Sawit terhadap Sifat Fisika dan Kimia Tanah serta Pertumbuhan dan Hasil Tanaman Kedelai pada Ultisols - Bakri Bakri; Sabaruddin Sabaruddin; LW Rahmadhoni (Seminar Nasional Lahan Suboptimal, 2021)
Bakri B, Sabaruddin S, Rahmadhoni LW. 2021. The effect of addition of palm oil mill liquid waste on physical and chemical properties of soil and growth and yield of soybeans on ultisols. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 47-57.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This research aims to study the effect of the application of Palm Oil Mill (POME) on the physical and chemical characteristics of the soil as well as the growth and yield of soybean (Glycine max L.). Field experiments were carried out on Ultisols soil in Bangka Regency, Bangka Belitung Islands Province. The treatments included chemical fertilizers (75 kg urea/ha, 100 kg SP-36/ha, 50 kg KCl/ha) without POME (L) and POME application at a dose of 75,000 L/ha (L1), 150,000 L/ha (L2), 225,000 L/ha (L3), and 300,000 L/ha (L4). The experiment used a simple randomized group design with 4 replications. The experimental results showed that POME application had a significant effect on soil K-dd at 30 DAP, several primary branches, and soybean yield per plot but had no significant effect on total pore space, permeability, pH, C-organic, and P-available at 30 DAP and 60 DAP and soil K-dd at 60 DAP and soybean plant height. The highest soybean yield was 2.72 tons/ha obtained by treatment L4 (300,000 L POME/ha).